PEMBERDAYAAN PENGRAJIN BATIK KAYU MENEMBUS PASAR EKSPOR MENUJU EKONOMI KERAKYATAN - Kiromim Baroroh; Sudji Munadi; Nur Hidayah (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
This paper gives an overview of wooden batik craftsmen empowerment activities in an effort to penetrate the market ekspor. Five main mission has been done to achieve good results include: awareness, organizing, regeneration companion, technical support and system management. It still needs to be addressed is in terms of awareness to exhibit at their own expense and courage to penetrate export markets by way of direct export is still lacking. They are still very dependent on the agent. SMEs focus on the production, however direct marketing is very difficult.Keywords: empowerment, wooden batik, export